2021
DOI: 10.1051/shsconf/20219207046
|View full text |Cite
|
Sign up to set email alerts
|

Georgian Labour Market during the Coronavirus Pandemic

Abstract: Research background: The paper analyzes and assesses the current situation in the Georgian labor market in the conditions of the pandemic. The article discusses the current, post pandemic state of the labour market in Georgia and the outcomes, impacts of Covid-19 on socio-economic situation. Purpose of the article: According to the present situation, it is necessary to create institutions and mechanisms that will ultimately provide the public as well as private sectors with highly qualified workforce, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…"In the second quarter of 2020 the employment rate decreased by 0.5 percentage points to 55.9%. In the II quarter, compared to the corresponding quarter of the previous year, the share of employees in the total employment rate decreased by 1.6 percentage points to 48.6%" [11] Nevertheless, research by Nino et al found that organizational conflicts have decreased. "Total number of conflict cases has decreased as work nature has changed.…”
Section: Conflict Managementmentioning
confidence: 97%
See 1 more Smart Citation
“…"In the second quarter of 2020 the employment rate decreased by 0.5 percentage points to 55.9%. In the II quarter, compared to the corresponding quarter of the previous year, the share of employees in the total employment rate decreased by 1.6 percentage points to 48.6%" [11] Nevertheless, research by Nino et al found that organizational conflicts have decreased. "Total number of conflict cases has decreased as work nature has changed.…”
Section: Conflict Managementmentioning
confidence: 97%
“…"In statistical and social studies unemployment is presented as Georgia's socioeconomic problem and represents one of the most pressing and important political issues for the country." [11] In this regard, the pandemic worsened the situation. "In the second quarter of 2020 the employment rate decreased by 0.5 percentage points to 55.9%.…”
Section: Conflict Managementmentioning
confidence: 99%
“…It should be underlined that in order to reduce poverty in our country, we should implement an active labour market policy, which will be organised by the government, and an adequate system of social protection for unemployed persons. Such as access to healthcare services and the implementation of focused government training programmes, which help unemployed persons in the future find a good job [37].…”
Section: Economicsmentioning
confidence: 99%
“…The COVID-19 pandemic has had an impact on the labour market, as noted by Paresashvili et al [16]. This has resulted in challenges for installers who are encountering obstacles in locating qualified personnel to perform installations.…”
Section: Impact Of Covid-19 On Pv Installationmentioning
confidence: 99%